2020
DOI: 10.1186/s43141-020-00091-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two phytochrome mutants of tomato (Micro-Tom cv.) reveals specific physiological, biochemical, and molecular responses under chilling stress

Abstract: Background Phytochromes are plant photoreceptors that have long been associated with photomorphogenesis in plants; however, more recently, their crucial role in the regulation of variety of abiotic stresses has been explored. Chilling stress is one of the abiotic factors that severely affect growth, development, and productivity of crops. In the present work, we have analyzed and compared physiological, biochemical, and molecular responses in two contrasting phytochrome mutants of tomato, namely aurea (aur) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…The background fluorescence signal, F o , was induced on 20 min dark-adapted leaves, by an inner light of about 2–3 μmol photons m −2 s −1 , at a frequency of 0.5 kHz. Previous experiments demonstrated that 20 min are sufficient to obtain complete re-oxidation of PSII reaction centers ( Shahzad et al, 2020 ). The maximum fluorescence level (F m ) in the dark-adapted state was determined with a 1 s saturating light pulse of about 6,000 μmol photons m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The background fluorescence signal, F o , was induced on 20 min dark-adapted leaves, by an inner light of about 2–3 μmol photons m −2 s −1 , at a frequency of 0.5 kHz. Previous experiments demonstrated that 20 min are sufficient to obtain complete re-oxidation of PSII reaction centers ( Shahzad et al, 2020 ). The maximum fluorescence level (F m ) in the dark-adapted state was determined with a 1 s saturating light pulse of about 6,000 μmol photons m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial effect of hp2 in stress tolerance may extend beyond heat stress due to the fact that flavonols play an important role in protecting against oxidative stress which accompanies many other environmental stresses, such as cold, drought, and nutrient starvation ( Nakabayashi et al, 2014 ; Zandalinas et al, 2017 ; Zhao et al, 2019 ; Song et al, 2020 ). Interestingly, a recent publication describes the tomato Micro-Tom high pigment 1 , a closely related mutant to hp2 , as chilling stress tolerant in terms of photosynthetic activity, activities of antioxidant enzymes, and accumulation of protecting osmolytes ( Shahzad et al, 2020 ). It would be of interest to test whether pollen characteristics, such as viability, germination capacity, and flavonol levels are playing a role also in hp1 under chilling and heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The fully expanded leaves were dark acclimated in the LI-6400XT leaf chamber for 30 min at 28 °C prior to measuring the minimum fluorescence (Fo) and maximum fluorescence (Fm). The maximum quantum yield of PSII (Fv/Fm) was calculated as (Fm − Fo)/Fm according to an earlier study [ 25 ]. The non-photochemical quenching (NPQ) coefficient was determined according to previous study [ 26 ].…”
Section: Methodsmentioning
confidence: 99%